Design and Implementation of a Web-Based Delivery Service for President University: A Case Study of President's Pick-Up - Dustin Mareo Istanto; Farhan Ali Ramadhan; Farhan Alwanda (President University, 2023)
The advent of web-based delivery services has brought about a revolutionary change in the transportation of packages and documents, offering unprecedented convenience and efficiency to users. In line with this trend, President's Pick-Up, a dedicated platform implemented with PHP and MySQL, emerged to cater to the package delivery needs of President University students. This thesis investigates the impact of President's Pick-Up as a web-based delivery service on user satisfaction, efficiency, and speed of package delivery within the President University community. Leveraging the power of PHP and MySQL, President's Pick-Up provides a user-friendly website platform for students to conveniently send packages to different dormitories on campus. The research evaluates the effectiveness of President's Pick-Up in meeting user needs, tracking package deliveries in real-time, and enhancing the overall package delivery experience for students. The study contributes valuable insights into PHP and MySQL-driven web-based delivery services and aims to guide future improvements in similar platforms catering to academic institutions.